Digital Information Board Using Rasberry Pi 3 Model B Based on Raspbian - Naufal Agung Pambudi; Ritzkal; Ade Hendri Hendrawan (Jurnal Mantik, 2021)
Digital Information Board (Digital Signage) is a digital content management application that has been programmed to be able to display a sequence of information or messages to the target audience / audience effectively, quickly, precisely and reliably. Digital signage pampers the audience's eyes in providing an attractive and attractive visual spectacle, various messages or multimedia format information can be played smoothly, including images, videos, scroll text / running text, charts, graphs, schedules, news, weather presented dynamically using electronic display media such as LCD TVs, Plasma TVs, Projectors, and Digital Billboards as output. This research was carried out by utilizing the Rasberry Pi 3 Model B microcontroller as a webserver for digital information board media (digital signage) then with a WEB display as the output of the displayed display. Testing is carried out on the WEB, so that the web is made as expected and also valid. With the Digital Information Board using Rasberry, the information or message conveyed to the audience / audience will be more effective and efficient.